PENGARUH FREKUENSI KONTRASEPSI SUNTIK DMPA TERHADAP KENAIKAN BERAT BADAN PADA AKSEPTOR KONTRASEPSI SUNTIK DMPA - Haryani, Dewi Dwi; Santjaka, Aris; ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Family Planning in one of the based and prominent healthy preventive service for women. Mostly Injection contraception device is used by mothers. Beside has benefits contraception device also has many side effects especially for DMPA injection Family planning device, it can raise body weight. Progesterone hormone is one of the causes that increase body weight.To find out the influence of DMPA injection contraception frequency toward the raising of body weight to DMPA injection contraception acceptor in BPS Dian Yuni Purwani Desa Klahang Kecamatan Sokaraja Kabupaten Banyumas. This research belongs to analytical research with cross sectional design and technique of collecting data based on inklusi criteria. The number of the sample is 76 respondents. The data is collected by using observation technique. The analysis used univariat analysis and bivariat analysis. The statistical test with linear regression result the value of thitung = 3,773, R= 0,042 including weak influence category, the influence of DMPA injection contraception frequency toward the rising of body weight in DMPA injection contraception acceptor is 16,1 %. It means that the more DMPA injection is given then the body weight will raise. There is influenceof DMPA injection contraception frequency toward the raising of body weight to DMPA injection contraception acceptor in BPS Dian Yuni Purwani Desa Klahang Kecamatan Sokaraja Kabupaten Banyumas. Midwife should gives information to DMPA injection contraception acceptor for trying to use the other contraception device which does no contains hormone such as IUD or tubektomi at acceptor who is > 35 years old with high parity. Â  Key words : injection frequency, raise of body weight, injection contraception DMPA